Conditions of Chemical Parameters of the Anahoni River to Detect Water Quality - M. Sehol; Kasmawati; Rosita Mangesa; Irsan (PT Inovasi Pratama Internasional, 2023)
This study aims to analyze the water quality of the Anahoni river due to gold mining by covering chemical parameters (pH, DO, BOD, COD, heavy metal mercury (Hg), iron (Fe), copper (Cu), Cadmium (Cd), Arsenic (As) ) and cyanide (CN).Metal mercury, iron, copper, cadmium, arsenic, and cyanide were tested at the Proling Bogor Agricultural Institute (IPB) laboratory. Meanwhile, DO, BOD parameters were analyzed at the Maluku Provincial Health Office Laboratory. pH and temperature parameters were carried out measured in situ. The pH value of the waters was obtained in the range of 7.1-10.5.The measured DO concentration has a value that varies in the range of 4.6-10.4 mg/L.The concentration of BOD has a value in the range of 0.5-10 .25 mg/L. COD concentrations have values ​​in the range of 1.7-12.11 mg/L. Hg, Fe, Cu, As, and CN metals were detected in water and sediments.